Developing a Religious Literacy-Based PKM Model to Strengthen Religious Moderation at Ibnurusyd Islamic College, Lampung - Syarifuddin Zuhri, Ahmad; Jumadi, Jumadi; Tri Kurniati, Erniza; Safitri, Heni; Marlina, Leni (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
This community service study aims to develop an innovative religious literacy–based model to strengthen religious moderation among students at Sekolah Tinggi Agama Islam (STAI) Ibnurusyd Lampung. The program involved 60 undergraduate students and 5 lecturers, who served as facilitators and co-researchers. It was implemented through structured educational activities, including religious literacy training, cross-perspective discussion forums, and reflective writing workshops. These activities were designed to address students’ limited cross-perspective understanding of religion and tendencies toward exclusive interpretations. The program employed a Participatory Action Research (PAR) approach, positioning students and lecturers as active participants in collaborative learning and reflective action. The PAR cycle was conducted over three months and consisted of problem identification, participatory planning, action implementation, observation, and reflective evaluation. Program outcomes were measured using pre-test and post-test questionnaires, interviews, participatory observation, and reflective journals. Quantitative results show an average increase of 32% in students’ understanding of religious moderation, particularly in tolerance, balance (tawazun), justice (i‘tidal), and openness to differences. Qualitative findings indicate positive attitudinal shifts, including increased empathy, greater inclusivity, and enhanced collaboration. The program developed an innovative, religious literacy–based model that integrates cognitive, affective, and practical dimensions, reflecting a collaborative approach and potential replicability in other Islamic higher education institutions.